2021
DOI: 10.1016/j.jpeds.2020.12.060
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of the Novel Coronavirus Disease 2019 on Therapy Service Delivery for Children with Disabilities

Abstract: Objective To assess the impact of the novel coronavirus disease 2019 (COVID-19) pandemic on the delivery of, and parent satisfaction with, therapy services for children with disabilities in early intervention, school, and outpatient settings.Study design There were 207 parents of children with disabilities who completed a web-based survey about their child[ren]'s access to, and satisfaction with, therapy services during COVID-19. Parents also completed the Family-Provider Partnership Scale and the Telehealth S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
83
0
5

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(100 citation statements)
references
References 29 publications
9
83
0
5
Order By: Relevance
“…In comparison, the majority of children receiving in-home or school-based services such as physical, speech, and occupational therapies had these services cancelled or shifted to telehealth. 37 , 38 , 39 , 40 , 41 …”
Section: Discussionmentioning
confidence: 99%
“…In comparison, the majority of children receiving in-home or school-based services such as physical, speech, and occupational therapies had these services cancelled or shifted to telehealth. 37 , 38 , 39 , 40 , 41 …”
Section: Discussionmentioning
confidence: 99%
“…The reliance on families for remote learning may have placed additional responsibilities on families that were adjusting to public health measures and changes in family and work routines (Goldschmidt, 2020). There is some evidence that families with children with disabilities may have had a harder time adjusting to remote learning and meeting their children's developmental needs during the pandemic than families with children without disabilities (Murphy et al, 2020). This may explain why ECSE teachers spent more time providing support to families than ECE teachers.…”
Section: Remote Learning Approachmentioning
confidence: 99%
“…Generally, participants felt that telehealth would be more useful for medical appointments after the COVID-19 pandemic ends. Another study by Murphy A et al [21] revealed that 36% of participants reported medium satisfaction and 21% reported high satisfaction regarding provided health services during the COVID-19 pandemic. Access to telehealth significantly predicted overall satisfaction -80% of the families without telehealth access reported low satisfaction compared to 30% of families with access to telehealth.…”
Section: Discussionmentioning
confidence: 97%